Neuroticism and Depression in Children: The Role of Cognitive Emotion Regulation Strategies. Issue 2 (3rd March 2016) - Andrés, María Laura; Richaud de Minzi, María Cristina; Castañeiras, Claudia; Canet-Juric, Lorena; Rodríguez-Carvajal, Raquel
ABSTRACT: This study's general objective was to analyze whether different types of cognitive emotion regulation strategies (CERS), namely adaptive strategies—specifically positive refocusing and positive reappraisal—and maladaptive strategies—self-blame, catastrophizing, and rumination—mediated the neuroticism-depression relationship in children 9–12 years old, and whether gender and school transition moderated the relationships proposed. A self-reporting measure was administered to 315 children to evaluate said variables. The resulting data were analyzed using structural equations. The study verified that maladaptive CERS partially mediated neuroticism's relationship with depression, while adaptive CERS, though negatively associated with depression, did not show a mediating effect on this relationship. The results provide evidence of the mediating function of maladaptive CERS on the neuroticism-depression relationship. Gender and school transition did not moderate the relationships proposed. Because, by their very nature, these strategies are modifiable, these results constitute an important finding that can be transferred to the design and content of child mental health prevention and promotion programs.